Does Attribute Framing in Discrete Choice Experiments Influence Willingness to Pay? Results from a Discrete Choice Experiment in Screening for Colorectal Cancer - Howard, Kirsten; Salkeld, Glenn (Value in health, 2009)
Recent reviews of discrete choice methodology identified methodological issues warranting further exploration, including the issue of “framing.” The objective of this study was to conduct a methodological exploration of the effect of attribute framing on marginal rates of substitution (MRS), including willingness to pay (WTP) from a discrete choice experiment (DCE), within the context of colorectal cancer screening preferences. The survey, a fractional factorial design of a two-alternative, unlabeled experiment, was mailed to a sample of 1920 subjects in NSW, Australia. Participants were randomized to one of four alternative “frames” of information. Attributes included: accuracy of the test for finding cancers, accuracy of the test for finding large polyps, how good the test is at saying you don't have cancer, cost, dietary and medication restrictions and sample collection. A mixed logit model was used to estimate preferences; MRS between attributes, including WTP, was calculated. A total of 1157 surveys from 1920 (60.2%) were returned. Accuracy of the test for finding cancer was most likely to influence choice of test, followed by accuracy of the test for finding large polyps. Under some circumstances, framing of the attributes (e.g., cancers found vs. cancers missed) influenced the relative importance of attributes. Attribute framing significantly influenced estimates of WTP, and benefit: harm trade-offs that were calculated from MRS. Attribute framing can influence willingness to pay and benefit: harm trade-offs from DCEs. Appropriate design and analysis methods should be explored to further characterize the influence and extent of framing in discrete choice studies.